Usage of differential pressure gas, reducible at GDS and GDC for receipt of electricity and heat - Черных, Анатолий Петрович; Васильев, Анатолий Иосифович (Eastern-European Journal of Enterprise Technologies, 2013)
Bearing on the main gas mains gas possesses potential energy of the compressed condition and kinetic energy of movement on a pipe. The basic part of this energy dissipates on items of pressure decline of gas. With the purpose of useful use of pressure difference NPP "Gazelektropribor" sources of the electric power and heat are developed and introduced on the basis of the turbine placed in a gas stream. In these installations it is realized saving energy, independent, non-polluting process of reception of an electricity and heat. Perspective direction is application of high-circulating turbines having high values efficiency and to specific power, which through a reducing gear, lowering frequency of rotation of output billow, unite with the rotor of turbogenerator. At an identical work overfall of pressure of gas, as compared to a direct-drive chart, required expense of gas in this setting less than approximately на30 %.